Rumen-Protected Amino Acids: Their Importance and Effects on Performance, Heat Stress, and Immunity in Cattle - Salur Srihitha; Mekapothula Himabindu; Sikhamoni Haloi; Om Prakash Reddy (Indian Journal of Animal Nutrition, 2025)
Balanced nutrition is crucial for optimum dairy cow production, with protein being particularly important for productivity and reproductive performance. Ruminal microorganisms utilize diet components to synthesize microbial protein (MCP), which is then digested in the small intestine (SI). The protein and amino acids produced by microbial processes are inadequate for optimal daily production, leading to the current practice of supplementing ruminant diets with additional amino acids. Bacteria in the rumen can break down free amino acids, necessitating the supplementation of amino acids in a protected form to ensure their stability in the rumen and absorption post-ruminally for metabolic purposes. The small intestine (SI) is the primary site of amino acid absorption, so it is crucial to protect amino acids from ruminal degradation and direct them to the absorption sites. Beyond their role in milk production, amino acids are important for immune function in animals and have been shown to alleviate oxidative stress. Low-protein diets supplemented with rumen-protected amino acids (RPAA) can replace high-protein diets in summer, as increased protein metabolism can result in higher heat production and subsequent stress.